A Comparative Study on The Electrochemical Properties of Hydrothermal and Solid-State Methods in The NCM Synthesis for Lithium Ion Battery Application - Sylvia Ayu Pradanawati; Eduardus Budi Nursanto; Afif Thufail; Ahmad Zaky Raihan; Sugianto Sugianto; Haryo Satriya Oktaviano; Hanida Nilasary; Achmad Subhan; Agung Nugroho (ASEAN Journal of Chemical Engineering, 2022)
In this article, we report and compare the synthesis method of the active cathode materials based on nickel‐cobalt‐manganese (NCM) for lithium-ion battery application. We evaluate the hydrothermal and solid-state reaction method in NCM-622 synthesis, the material characterizations, and the battery performance. Based on the analytical results using X-ray diffraction (XRD), particles synthesized using hydrothermal and solid-state methods exhibit a highly crystalline NCM phase. NCM particles synthesized using solid-state reaction exhibit high-rate performance up to 10 C. The electrochemical impedance spectroscopy analysis shows that the charge transfer resistance (Rct) of NCM synthesized by the solid-state reaction (SSR) method was 25.9% lower than hydrothermal. Meanwhile, the ionic diffusivity of the SSR sample was 38.5% higher than the hydrothermal sample. These two factors lead to better performance when tested in a lithium-ion battery.